CORONAL BACTERIAL LEAKAGE ASSESSMENT OF DIRECT INLAY COMPOSITE VERSUS INDIRECT CERAMIC RESTORATION IN (MOD) CAVITY OF ENDODONTICALLY TREATED MAXILLARY PREMOLARS WITH A SINGLE ROOT - Mohammed E. Rokaya; Fahd M. Hadhoud; Karam Hamada Ahmed Khalaf; Mohamed Ahmed Mahmoud Hamed; Safwat S Elwaseef; Ehab Mohamed Kamal; Ahmed Ata Abd El-ghany; Zainab Refaey El Sharkawy; Inas M. Mohamed; Dana Saeed Abd Elmonem El gemaie (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Aim: To evaluate the bacterial coronal leakage assessment of direct inlay composite versus indirect ceramic restoration of (MOD) cavity in endodontically treated maxillary premolars with single root. Method: 30 human maxillary premolars with single root of fully developed apex extracted were selected. Every tooth has decoronated to 3 mm coronal to cementoenamel junction using diamond disc bur for standardization. ProTaper rotating tools were employed to chemo mechanically prepare the root canals and for radicular preparation to size F3 finishing file. ProTaper obturators #F3 were employed to obturate the canals and resin sealer (ADSEAL) were used for filling the canals via the lateral condensation method. Two mm apically of the coronal gutta percha was removed to make a space for liner material. Above the gutta-percha to the level pulp chamber floor, glass ionomer restorative was utilized as a liner material. The premolars were allocated into 2 identical test groups (group 1&2) of 10 premolars each in accordance with the final restoration techniques (direct & indirect) with other two groups of positive control with 5 intact teeth, and negative control with 5 teeth with empty (MOD) preparation of the cavity following endodontic therapy without placement of the final restoration. The specimens were subjected to thermocycling then bacterial coronal leakage assessment was done for all teeth by using two-chamber. Results: Group 1: Direct Inlay (Composite Resin) recorded 43% leakage versus 57 % without leakage. On other hand Group 2: Indirect (Ceramic Inlay) recorded 34% leakage versus 66 % without leakage, but without statistically significant differences. Conclusion: Ceramic Inlay as indirect technique of coronal restoration of endodontically treated teeth gives superior results in relation to direct Inlay Composite Resin in coronal bacterial leakage assessment.